Factor Intensities in Manufacturing Industries in Pakistan (The Pakistan Development Review, 1970)
The choice of technology in the developing countries has been a subject matter of considerable theoretical and empirical investigation. That labour-abundant economy like Pakistan should opt for labour-intensive technology in order to maximise income and employment has been widely recommended. There has, however, been long-standing controversy as to whether, and how far, the choice of labour-intensive technology slows down the rate of growth of income as against the maximisation of current income by increasing the share of wages in income which are assumed to be wholly or mostly consumed and by correspondingly reducing the share of profits which are assumed to add mainly to the invisible surplus and thus to increase the rate of capital accumulation. This line of reasoning postulates that a developing economy has more or less free choice between alternative techniques, embodying different degrees of labour intensity and has, in addition, adequate instruments of policy at its disposal to regulate the choice of technology in the public and private sectors of the economy; it further seems to imply that it has very inadequate or ineffective instruments of policy at its disposal to alter the disposition of income between savings and investment, once the technology and its attendant distribution of income between wages and profits are given. The feasibility or the effectiveness of the various fiscal instruments for increasing the rate of saving in a developing economy has often been discussed, however, there is very little empirical analysis of the existing pattern of technology as well as of the limitations on the choice of technology in a country like Pakistan which imports technology mainly under foreign aid tied to the purchases in the individual aid-giving countries which happen to grant loan for individual, particular capital projects.